Clinicopathological Features and Outcomes Comparing Patients With Invasive Ductal and Lobular Breast Cancer. (14th October 2022) - Oesterreich, Steffi; Nasrazadani, Azadeh; Zou, Jian; Carleton, Neil; Onger, Tiffany; Wright, Matthew D; Li, Yujia; Demanelis, Kathryn; Ramaswamy, Bhuvaneswari; Tseng, George; Lee, Adrian V; Williams, Nicole; et al.
Abstract: Background: There is increasing interest in better understanding the biology and clinical presentation of invasive lobular cancer (ILC), which is the most common special histological subtype of breast cancer. Limited large contemporary data sets are available allowing comparison of clinicopathologic features between ILC and invasive ductal cancer (IDC). Methods: The Great Lakes Breast Cancer Consortium was formed to compare clinical behavior of ILC (n = 3617) and IDC (n = 30 045) from 33 662 patients treated between 1990 and 2017 at 3 large clinical centers. We used Kaplan-Meier analysis, Cox proportional hazards modeling, and propensity score matching to evaluate treatment differences and outcomes. All statistical testing used 2-sided P values. Results: Compared with IDC, patients with ILC were more frequently diagnosed at later stages and with more lymph node involvement (corrected P  < .001). Estrogen receptor–positive ILCs were of lower grade (grade 1 and 2: 90% in ILC vs 72% in IDC) but larger in size (T3 and 4: 14.3% in ILC vs 3.4% in IDC) (corrected P  < .001), and since 1990, the mean ILC size detected at diagnosis increased yearly. Patients with estrogen receptor (ER)–positive ILC underwent statistically significantly more mastectomies compared with ER-positive IDC (57% vs 46%). Using Kaplan-Meier analysis, patients with ER-positive ILC had statistically significantly worse disease-free survival and overall survival than ER-positive IDC although 6 times more IDCs were classified as high risk by OncotypeDx Breast Recurrence Score assay. Conclusions: This large, retrospective, collaborative analysis with 3 clinical centers identified meaningful differences in clinicopathological features between ILC and IDC, providing further evidence that these are 2 different entities requiring different clinical management.